2008
DOI: 10.3310/hta12060
|View full text |Cite
|
Sign up to set email alerts
|

Methods of prediction and prevention of pre-eclampsia: systematic reviews of accuracy and effectiveness literature with economic modelling

Abstract: The tests evaluated are not sufficiently accurate, in our opinion, to suggest their routine use in clinical practice. Calcium and antiplatelet agents, primarily low-dose aspirin, were the interventions shown to prevent pre-eclampsia. The most cost-effective approach to reducing pre-eclampsia is likely to be the provision of an effective, affordable and safe intervention applied to all mothers without prior testing to assess levels of risk. It is probably premature to suggest the implementation of a treat-all i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
172
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(180 citation statements)
references
References 0 publications
1
172
1
6
Order By: Relevance
“…After scrutiny, two references were excluded because they were meeting abstracts 93,94 that duplicated existing full-text references, and one was excluded because it was a systematic review that did not include any relevant index tests. 95 This systematic review, by Meads et al, 95 reviewed diagnostic methods for PE, but did not include any of this assessment's index tests. The remaining six references were three published full-text articles 33,39,96 that reported on three unique studies, and three confidential unpublished references that reported on two economic analyses provided by companies submitting evidence under the NICE Diagnostic Assessments process: Alere, Inc. 97,98 and Roche Diagnostics.…”
Section: Results Of the Review Of Economic Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…After scrutiny, two references were excluded because they were meeting abstracts 93,94 that duplicated existing full-text references, and one was excluded because it was a systematic review that did not include any relevant index tests. 95 This systematic review, by Meads et al, 95 reviewed diagnostic methods for PE, but did not include any of this assessment's index tests. The remaining six references were three published full-text articles 33,39,96 that reported on three unique studies, and three confidential unpublished references that reported on two economic analyses provided by companies submitting evidence under the NICE Diagnostic Assessments process: Alere, Inc. 97,98 and Roche Diagnostics.…”
Section: Results Of the Review Of Economic Studiesmentioning
confidence: 99%
“…Of the 1972 potentially relevant references originally identified in the searches of test accuracy studies (see Chapter 4, Quantity and quality of research available), six 33,39,[93][94][95][96] appeared to provide information about economic studies and were retrieved for further scrutiny ( Figure 6). Three further documents reporting economic analyses were provided by companies in confidence, as part of the NICE Diagnostics Full-text articles retrieved (n = 9)…”
Section: Results Of the Review Of Economic Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A prevenção da eclâmpsia poderá ser alcançada mediante uma efetiva assistência pré-natal na atenção primária, complementada pela atenção secundária aos grupos de risco. 5,8 Até que se tenha diagnóstico diferencial, a convulsão em gestação avançada deve ser considerada como diagnóstico de eclâmpsia, e os melhores resultados maternos e perinatais são obtidos pela adoção de protocolos padronizados em serviços de nível terciário. Orientase a conduta assistencial para medidas gerais de suporte cardiorrespiratório, terapia anticonvulsivante, tratamento anti-hipertensivo e conduta obstétrica resolutiva.…”
Section: Introductionunclassified